Telaah Pemikiran Nurcholish Madjid Terhadap Politik Identitas - Muhammad Nur Ilham; Darussalam Syamsuddin; Syahrir Karim (Tasamuh: Jurnal Studi Islam, 2024)
This research aims to determine Nurcholish Madjid's political thinking style. This research is library research or library study using a philosophical and historical approach. The data sources used are primary and secondary data sources. Primary data sources in this research are books written directly by Nurcholish Madjid, as well as books that are relevant to the discussion, while secondary data in this research are relevant literature materials that discuss identity politics. The data collection method in this research uses direct quotation and indirect quotation methods. The data analysis technique used in this research is content analysis technique. The research results show that Nurcholish Madjid's political thinking style is characterized by inclusiveness, pluralism and universal Islamic values. Madjid believes that Islamic values ​​should be applied in social life without linking them to religious-based political parties. He also advocates democracy, human rights, and education that emphasizes tolerance and pluralism. Background to the emergence of the jargon "Islam yes, Islamic parties no". This is a concern. He believes that Islamic political parties tend to divide society and are used for short-term political interests by elites. According to Nurcholish Madjid, the relevance of the jargon "Islam Yes, Islamic Party No" to the phenomenon of identity politics in Indonesia is very significant. This jargon teaches the importance of pluralism and inclusiveness in politics, so that it can reduce polarization and sectarianism in society.